Importance of GPCR-Mediated Microglial Activation in Alzheimer’s Disease - Haque, Md. Ezazul; Kim, In-Su; Jakaria, Md.; Akther, Mahbuba; Choi, Dong-Kug (Frontiers in Cellular Neuroscience, 2018)
Alzheimer`s disease (AD) is progressive neurodegenerative disorder associated with impairment of cognition, memory deficits, and behavioral abnormalities. Accumulation of amyloid Beta (Aβ) is a characteristic hallmark of AD. Microglia expresses several GPCRs that are activated by neurotransmitter and modulate microglial activation and polarization phenotype that can have both protective and detrimental effects. Microglial GPCRs are also involved in Aβ binding and clearance through triggering multiple inflammatory responses. In addition, microglial GPCRs regulate Aβ degradation and APP proteolysis. However, there is still lack of insights in the mechanistic link between GPCR mediated microglial activation and its pathological consequences in the AD. Although the currently available drugs for the treatment of AD are symptomatic and dominated by acetylcholinesterase (AchEI), the selection of a specific target that directly regulates the AD progression will be a potential source of therapeutic intervention. Here, we have highlighted the expression and distribution of various GPCRs linked with microglial activation in the AD and their potential to be a therapeutic target of AD.